Central area redd project [Ribble, Hodder and Lune catchments] - Lewis, J. (Environment Agency North West, 2000)
Redd counting is an integral part of most Fishery Officers duties. The number and distribution of salmonid redds throughout salmonid catchments provides invaluable information on the range and extent of spawning by both salmon and sea trout. A project was initiated by the Fisheries Science and Management Team of Central Area, North West Region in England in liaison with the Flood Defence function. The main objective of this project was to assess redd count data for Central Area and attempt to quantify these data in order to produce a grading system that would highlight key salmonid spawning areas. By showing which were the main areas for salmon and sea trout spawning, better informed decisions could be made on whether or not in-stream Flood Defence works should be given the go-ahead. The main salmonid catchments in Central Area were broken into individual reaches, approximately 1 km in length. The number of redds in these individual reaches were then calculated and a density per lkm value was obtained for each reach. A grading system was devised which involved looking at the range of density per km values and dividing this by five to produce 5 classes, A - E. A sixth class (F) was used where the density per Ion value was 0.00. This grading system was calculated at two levels of detail. Grades for salmon and sea trout were produced for each individual catchment and also on an Area-wide level. Maps were produced using a range of colours to represent the grade for each reach. These maps provide a highly useful overview of the status of salmonid spawning for each catchment over individual years and highlight the key salmon and sea trout spawning areas in each catchment. These maps and the associated summary data should now provide Flood Defence and Fisheries staff with a fairly detailed overview of the status of spawning in any location within the. main salmonid catchments in Central Area. Although these maps are very useful they should only be used as a guide. The current practice of consulting with the local ...